GASTRIC, LIVERAND RENAL LESIONS ASSOCIATED TO THE SYNDROME OF GASTRIC ULCERS IN THOROUGHBRED HORSES - Morales B., Abelardo (2011)
The aim of this study was to describe gastric, hepatic, and renal lesions inThoroughbred Racing horses associated to the equine gastric ulcer syndrome. Thirtyhorses with a history of gastric ulcer syndrome and recurrent colic during 2006 to 2007 atthe Race Track «La Rinconada», Caracas, Venezuela were evaluated. Horses were euthanized and the necropsy was conducted. Tissue samples were collected from stomach,liver and kidney, and processed by conventional histological methods. In the stomach,the mucosa was intact but areas of hyperaemia and hyperkeratosis were observed in 6cases, multifocal small erosions or ulcers in 6 cases, multifocal large ulcers with areas ofextensive erosion in 12 cases and extensive areas of ulceration with exposure of thesubmucosa in 6 cases. The macroscopic evaluation of the liver showed evidenthepatomegaly in 22 cases and lobular pattern in 18 cases. The kidneys showed severecongestion in all cases, loss of cortico-medullar ratio in 20 cases, cortical necrosis in 18cases, acute tubular necrosis in all cases, papillary necrosis in 6 cases, and adherence ofthe capsule with interstitial fibroplasia in 4 cases. Lesions in the gastric mucosa, liver andkidney were associated with extended treatment with non-steroidal anti-inflammatorydrugs